Work-from-Home Impact on Income Satisfaction - Krasulja, Nevena; Zubović, Jovan; Radojević, Ivana (Industrija, 2014)
In this paper authors have attempted to discover if working from home influences person’s income satisfaction. In the paper there has been given review of the issue of working from home impact as well as some results from other research. Methodology used in empirical section is based on factor analysis which has been used to reduce number of variables to a single one described as “Importance of work from home”. Moreover there have been done several regression analyses which aimed to show what impact different factors have on the income satisfaction level. Results from the research show that WFH has two-fold impact on income satisfaction both in the form of subjective perspective of the WFH as well as on the objective fact on whether person is currently working-from-home.